Private lives and public power: Norwich merchants' houses between the 14th and 16th centuries - King, Chris (Maney Publishing, 2015)
This chapter discusses the surviving examples of large merchants’ houses in the city of Norwich dating between the 14th and 16th centuries. These were the residences of families who dominated the economic and political life of the medieval and early modern city, and possess impressive domestic accommodation arranged around an open hall, alongside extensive undercroft spaces for the storage and display of merchandise. The eight remaining examples of great halls, with their screens-passages and bay windows, are a unique survival for an English provincial city. It is argued that these were important not simply for the expression of private status but as locales for the negotiation of shared cultural identities and public, civic authority within the mercantile elite. In the 16th century, many mercantile residences in Norwich were rebuilt adopting innovative plans and decorative elements, whilst other merchants chose to retain their medieval great halls as self-conscious symbols of personal and corporate honour and legitimacy.